It feels like Armageddon: identification with a female personality-disordered offender at a time of cultural, political and personal attack. Issue 3 (27th May 2017) - Short, Helen
ABSTRACT: This paper describes work undertaken at a secure unit for female mentally-disordered offenders in the United Kingdom. It addresses the use of psychoanalytic music therapy within the institution, in particular using material pertaining to an individual diagnosed with a psychotic illness and personality disorder, detained long term in an acute ward of the hospital. The work took place at a time when huge cuts to the UK's National Health Service (NHS) were being implemented, and arts therapies were one of the resources that had been downscaled. A theme running throughout the paper examines the author's personal challenges as a newly qualified therapist and the way in which the institutional dynamics impacted upon the work. Also explored are some of the challenges the therapist faced that arose as a result of shared experiences that resonated strongly between client and therapist. The main body of the paper addresses key psychoanalytic concepts that underpinned the work. In music therapy, a growing body of clinical work focusing upon attachment and mentalisation is emerging, and in also considering the complex needs and ways of relating of the client from these perspectives, the author hopes to contribute towards this.